(untitled) (African Journal for Industrial and Applied Mathematics, 2025)
Interoperability cost analysis is a continuous trend in enterprise information systems. Researchers have made the most significant contributions in this field. The problem we address is to show how to optimize interoperability costs within a networked enterprise. To overcome this issue, we have used a genetic algorithm in which, the fitness function that we have defined is a new model for optimizing the interoperability cost. To show how organizations validate and verify the solutions obtained through interoperability cost analysis and what measures are taken to ensure the accuracy and reliability of the results, we have conducted a case study within a networked enterprise. The results of the interoperability cost analysis show that the inter-organizational business process studied is not adapted to the interoperable information system and does not allow the evolution of the network after a certain number of years.